Hypertension Policy Analysis Allowing for Group-Specific Diagnostic Strategies - Heidenberger, K. (Methods of Information in Medicine, 1982)
The paper describes the structure and operation as well as the performance data of a computer system designed for interactive, quantitative policy analysis in the field of hypertension management, focusing mainly on the problem of selecting group-specific diagnostic strategies under resource constraints. Its overall goal is insight, not numbers. The system’s design incorporates stringent criteria including flexibility, expandability, adaptability to varied populations, portability and low-cost operation.
Keywords: Policy Analysis; Hypertension; Interactive Selection of Diagnostic Strategies